Students’ Attitudes Towards Career in the Tourism Industry – Implications for Tacit Knowledge Management - Marlena A. Bednarska; Marcin Olszewski (Journal of Entrepreneurship, Management and Innovation)

(untitled)
The success of tacit knowledge management lies in firms’ capabilities to attract and retain employees possessing unique knowledge. The purpose of the paper is to investigate students’ attitudes towards career in tourism in the context of tacit knowledge management. The study was conducted on the group of 345 undergraduates and graduates enrolled in tourism and hospitality studies in Poznan. Research revealed that majority of students plan short-term career in tourism, which entails tacit knowledge leakage outside the tourism industry. It was also found that students’ attitudes towards tourism careers are significantly influenced by previous work experience and satisfaction with the studies.